Hubungan Accessibility dengan Citra Rumah Sakit di Ruang Rawat Inap RSUD Lamaddukkelleng Sengkang - Andi Mikhrunnisai; A Nur Azizah; Khaeriah B; Ruslang Ruslang; Nurdiana Nurdiana (Journal Research of Health Administration and Public Health (JRHAPH), 2025)
The image of a hospital reflects the public's perception of the quality of services provided by a healthcare institution. This perception is shaped by various factors, one of which is accessibility. Easy and adequate access such as a strategic location, available transportation, and convenience in obtaining services is believed to enhance patient satisfaction and contribute to a positive image of the hospital. This study aims to determine the relationship between accessibility and hospital image among inpatient service users at RSUD Lamaddukkelleng Sengkang. This research employed a quantitative design with a cross-sectional approach. A total of 100 respondents were selected from a population of 14,204 inpatients using proportional stratified random sampling. Inclusion criteria included patients who were hospitalized for more than 2×24 hours, were conscious, able to be interviewed, and for children, accompanied by a parent or legal guardian. Data were collected using a structured questionnaire and analyzed using the Chi-Square test with the assistance of SPSS version 16. The results showed that 73% of respondents rated hospital accessibility as adequate, and 72% perceived the hospital image as positive. The statistical analysis yielded a p-value of 0.000, indicating a significant relationship between accessibility and hospital image. Therefore, the better the patient's access to hospital services, the more positive the hospital's image in the public's perception.